Analysis and identification of tyrosine phosphorylated proteins in hemocytes of Litopenaeus vannamei infected with WSSV. Issue 82 (November 2018) - Tang, Xiaoqian; Li, Xiaoai; Zhai, Fude; Xing, Jing; Sheng, Xiuzhen; Zhan, Wenbin
Abstract: Previous studies have demonstrated that protein tyrosine phosphorylation plays an important role in WSSV infection. In the present work, in order to further elucidate the potential role of protein tyrosine phosphorylation in white spot syndrome virus (WSSV) infection. The expression variation of tyrosine phosphorylated proteins in hemocytes of shrimp ( Litopenaeus vannamei ) after WSSV infection were examined by flow cytometric immunofluorescence assay (FCIFA) and enzyme linked immunosorbent assay (ELISA), and results showed that the level of protein tyrosine phosphorylation in hemocytes fluctuated significantly after WSSV infection and exhibited two peaks at 6 and 24 h post infection (hpi). Meanwhile, tyrosine phosphorylated proteins in hemocytes after WSSV infection were also detected by cell immunofluorescence, and results showed that the fluorescence intensity in hemocytes was altered with the course of WSSV infection and showed stronger fluorescent signals at 6 and 24 hpi compared to other time points. Furthermore, two dimensional gel electrophoresis (2-DE) and 2-DE western blotting were applied to identify the differentially expressed tyrosine phosphorylated proteins in hemocytes before and after WSSV infection. The result of 2-DE western blotting showed that there were nine tyrosine phosphorylated proteins in the hemocytes of healthy shrimp, whereas twenty-one tyrosine phosphorylated proteins were detected in the hemocytes of shrimp at 6hpi. Then, the differential tyrosine phosphorylated proteins were analyzed by Mass Spectrometry (MS), and eight of them were identified to be sodium/potassium-transporting ATPase subunit alpha, ubiquitin/ribosomal L40 fusion protein, actin-D, phosphopyruvate hydratase, beta-actin, ATP synthase subunit beta, receptor for activated protein kinase c1 and protein disulfide-isomerase. Moreover, the expression levels of sodium/potassium-transporting ATPase subunit alpha, ubiquitin/ribosomal L40 fusion protein, phosphopyruvate hydratase, ATP synthase subunit beta, receptor for activated protein kinase c1 and protein disulfide-isomerase were examined to be up-regulated post WSSV infection by quantitative real-time RT-PCR. Taken together, these results demonstrated that protein tyrosine phosphorylation was involved in the process of WSSV infection, which might play an important role in the immune response to WSSV infection in shrimp. Highlights: The level of protein tyrosine phosphorylation in hemocyte exhibited two peaks post WSSV infection. Tyrosine phosphorylated proteins were detected in hemocytes by cell immunofluorescence. 12 differentially tyrosine phosphorylated proteins were identified post WSSV infection.